2017
DOI: 10.2903/j.efsa.2017.4751
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness to set a group health based guidance value for nivalenol and its modified forms

Abstract: The EFSA Panel on Contaminants in the Food Chain (CONTAM) reviewed new studies on nivalenol since the previous opinion on nivalenol published in 2013, but as no new relevant data were identified the tolerable daily intake (TDI) for nivalenol (NIV) of 1.2 lg/kg body weight (bw) established on bases of immuno-and haematotoxicity in rats was retained. An acute reference dose (ARfD) of 14 lg/kg bw was established based on acute emetic events in mink. The only phase I metabolite of NIV identified is de-epoxy-nivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 63 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Similarly, in relation to the NIV, considering the potential risk of NIV3G hydrolysis in the human gastrointestinal tract and its co-occurrence with NIV in cereal grains, the EFSA concluded that NIV3G should also be included in the group Tolerable Daily Intake (TDI) and RfD together with NIV. Unfortunately, the scientific data on the presence of DON3G, and especially NIV3G in food, is still limited [25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in relation to the NIV, considering the potential risk of NIV3G hydrolysis in the human gastrointestinal tract and its co-occurrence with NIV in cereal grains, the EFSA concluded that NIV3G should also be included in the group Tolerable Daily Intake (TDI) and RfD together with NIV. Unfortunately, the scientific data on the presence of DON3G, and especially NIV3G in food, is still limited [25].…”
Section: Introductionmentioning
confidence: 99%
“…The worst scenario was obtained for NIV, with a mean PDI that is almost 30 folds higher than the reference TDI. An additional comment to be performed on the uncertainty around NIV and PDI, regards the excretion rate (ER) that, as reported in the literature, is derived from animal studies exclusively [ 19 ], therefore weighting to the uncertainty of the estimation. Moreover, the number of BM data available was critically low and coming from only two countries.…”
Section: Resultsmentioning
confidence: 99%
“…The ER of 72% was considered for DON according to Turner et al [ 48 ]. In the absence of human data, a value of animal urinary excretion rate of 1% was the best approximation value available for NIV [ 19 ]. An ER of 36.8% calculated for piglet, was considered for ZEN excretion in accordance with Gambacorta et al [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The chemical hazards of interest in food safety in Spain were already identified by the Committee, and the fellow was assigned to work on the emerging Fusarium mycotoxins enniatins (ENNs) and nivalenol (NIV); and pyrrolizidine alkaloids (PAs). ENNs and NIV were of interest because either they are not yet regulated, and/or they can co-occur with other mycotoxins (CONTAM Panel, 2014, 2017a, while PAs are a large group of plant secondary metabolites highly toxic to humans and animals (CONTAM Panel, 2017b). A literature search was conducted to identify relevant scientific data on ENNs, NIV and PAs relevant for food safety in Spain.…”
Section: 2mentioning
confidence: 99%